Public-private partnerships in the new EU member states : managing fiscal risks - Budina, Nina (World Bank working paper ;, 2007)
Public-private partnerships (PPPs) are popular around the world, in part because they allow governments to secure much-needed investment in public services without immediately having to raise taxes or borrow. Yet, PPPs pose a fiscal danger because a government's desire to avoid reporting immediate liabilities may blind it to future fiscal costs and risks. Although PPPs may not blemish governments' reported fiscal statements in the short term, they do create fiscal obligations. This increases fiscal vulnerability and can result in poorly-designed PPPs. The extent of the danger depends on the fi.